Education and training 14-19 curriculum, qualifications and organization - Hodgson, Ann, 1953-; Spours, Ken.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
This title provides a comprehensive and up-to-date account of the new 14-19 phase with a focus on A Levels and GCSEs, the new 14-19 diplomas, vocational learning, apprenticeships and institutional collaboration.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Education, Secondary -- England; Education, Secondary -- Wales; Post-compulsory education -- England; Post-compulsory education -- Wales; Electronic books